2008
DOI: 10.1037/a0012998
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating rigorous qualitative research in rehabilitation psychology.

Abstract: Qualitative research methods have much to contribute to theoretical and applied knowledge in rehabilitation psychology. However, as a discipline, rehabilitation psychology has been behind the curve in employing qualitative methods. Objectives: This article is a summary of the state of qualitative research in rehabilitation and an introduction to various methodological dimensions to consider in implementing qualitative rehabilitation psychology research. Types and examples of qualitative rehabilitation research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 65 publications
(69 reference statements)
0
49
0
Order By: Relevance
“…All participants were happy that the transcripts and provisional themes reflected their position on social activism and two participants added additional information that was incorporated into the data for analysis. An audit trail was maintained by keeping a research journal, including interview schedule development notes, reflections following the interview process and data analysis notes (Chwalisz, Shah, & Hand, 2008).…”
Section: Data Gathering and Analysismentioning
confidence: 99%
“…All participants were happy that the transcripts and provisional themes reflected their position on social activism and two participants added additional information that was incorporated into the data for analysis. An audit trail was maintained by keeping a research journal, including interview schedule development notes, reflections following the interview process and data analysis notes (Chwalisz, Shah, & Hand, 2008).…”
Section: Data Gathering and Analysismentioning
confidence: 99%
“…As previously discussed, research (Pattenaude, 2004& Chwalisz et al, 2008 has criticised the field of criminology for its reliance upon quantitative analysis to evaluate rehabilitative interventions. Authors (Pattenaude & Chwalisz) observe how quantitative analyses limit the depth of subjective understanding available to the critical thinker.…”
Section: The Research Problemmentioning
confidence: 99%
“…Whilst quantitative evaluations and meta analyses of New Zealand-based criminogenic rehabilitation programmes and international offence-related treatment interventions are in abundance Hollin & Palmer, 2009;McGuire, 2002;Polaschek et al 2005;Smith, Goggin &Gendreau, 2001 andTong &Farrington, 2006) the same cannot be said for qualitative methodologies. Chwalisz, Shah and Hand (2008) observed that "Qualitative research methods have much to contribute to theoretical and applied knowledge in rehabilitation psychology. However, as a discipline, rehabilitation psychology has been behind the curve in employing qualitative methods" (p.387).…”
Section: The Evolution Of Rehabilitative Treatmentmentioning
confidence: 99%
“…The assessment of the quality of qualitative studies was based on criteria held in the literature to denote high quality (Elliott et al, 1999;Daly et al, 2007;Chwalisz et al, 2008). Criteria included whether: the sampling frame was described, justified, or met; the framework for the study design, methodology and orientation disclosed; interviewer bias was addressed; the method of analysis was described; reliability and validity checks were included; data were clearly presented.…”
Section: Methodsmentioning
confidence: 99%